Study on the Adsorption, Diffusion and Permeation Selectivity of Shale Gas in Organics - Zhouhua Wang; Yun Li; Huang Liu; Fanhua Zeng; Ping Guo; Wei Jiang (Energies, 2017)
As kerogen is the main organic component in shale, the adsorption capacity, diffusion and permeability of the gas in kerogen plays an important role in shale gas production. Based on the molecular model of type II kerogen, an organic nanoporous structure was established. The Grand Canonical Monte Carlo (GCMC) and Molecular Dynamics (MD) methods were used to study the adsorption and diffusion capacity of mixed gas systems with different mole ratios of CO2 and CH4 in the foregoing nanoporous structure, and gas adsorption, isosteric heats of adsorption and self-diffusion coefficient were obtained. The selective permeation of gas components in the organic pores was further studied. The results show that CO2 and CH4 present physical adsorption in the organic nanopores. The adsorption capacity of CO2 is larger than that of CH4 in organic pores, but the self-diffusion coefficient of CH4 in mixed gas is larger than that of CO2. Moreover, the self-diffusion coefficient in the horizontal direction is larger than that in the vertical direction. The mixed gas pressure and mole ratio have limited effects on the isosteric heat and the self-diffusion of CH4 and CO2 adsorption. Regarding the analysis of mixed gas selective permeation, it is concluded that the adsorption selectivity of CO2 is larger than that of CH4 in the organic nanopores. The larger the CO2/CH4 mole ratio, the greater the adsorption and permeation selectivity of mixed gas in shale. The permeation process is mainly controlled by adsorption rather than diffusion. These results are expected to reveal the adsorption and diffusion mechanism of gas in shale organics, which has a great significance for further research.